Increasing resilience of electricity networks: Auctioning of priority supply to minimize outage costs - Anna Pechan; Gert Brunekreeft; Martin Palovic (Constructor University Bremen, Bremen Energy Research (BER), 2023)
This article presents an approach to minimize the outage costs during power supply disruptions and, thus, to incentivize efficient resilience investment by network users. The central problem to be solved is the information asymmetry between network operators and network users on outage and backup costs. We present an auction of priority positions among network users based on the Vickrey-Clarke-Groves mechanism, using a numerical example, to solve the problem. Under the mechanism, each winning bidder pays for the externality exerted on the other bidders by holding a certain position, excluding her own bid, which induces truthful bidding. Minimizing the damage from power supply interruptions, the mechanism improves the resilience of the power system not only in the short term but also in the long term.
Keywords: D44; K23; L94; 330; Resilience; electricity network; position auction; priority supply